LITERATURE REVIEW: THE EFFECTIVENESS OF THE PROBLEM-BASED LEARNING MODEL WITH A DIFFERENTIATED APPROACH IN IMPROVING THE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Firdaus, Muhammad; Suriansyah, Ahmad; Refia Rafianti, Wahdah (PT. Antis International Publisher, 2024)
Objective: This study aims to explore the integration of Problem-Based Learning (PBL) with differentiated instruction in elementary schools to enhance student engagement, academic achievement, and motivation. Methods: The research employed a mixed-method approach, combining quantitative assessments of academic performance with qualitative observations of student participation. Differentiated strategies were implemented to tailor content, processes, and products to various learning styles, including visual, auditory, and kinesthetic. Results: The integration of PBL and differentiated instruction significantly improved students' academic performance across subjects such as mathematics, science, and civics. It also fostered critical thinking, creativity, and collaboration, aligning with 21st-century skill development. Novelty: This study underscores the potential of combining PBL with differentiated approaches to address the diverse needs of learners and create adaptive, inclusive classrooms, providing a practical framework for overcoming challenges in modern education.